Sharing the non-monetary benefits of agricultural biodiversity - Raymond, R.; Fowler, Cary; International Plant Genetic Resources Institute (2001)
The Convention on Biological Diversity calls for benefits flowing from the use of biological diversity to be shared with the country of origin of the material. In the main, discussions around benefit sharing have focused on monetary benefits, with the sharing of such benefits often seen as a precondition to access. This approach, while welcome in its intent, has two inherent problems: it has led the significant non-monetary benefits that can be linked with the use of genetic resources to be downplayed or even disregarded; there is no agreed definition of 'country of origin.' Even if the meaning of country of origin could be universally accepted, a commercial plant variety is likely to have hundreds, if not thousands, of useful properties arising from parents originating in many countries. A system of access to plant genetic resources that requires individual benefit-sharing agreements with the countries of origin of all such properties would be exceedingly complicated. The cost of these numerous negotiations, let alone of determining the monetary value of the contribution of each country's genetic resource to the commercial variety, would be staggering. Such a system would surely be a disincentive to commercialization (assuming the costs would be borne by the commercial entity—by no means a foregone conclusion). Importantly, it would also almost certainly impede the international flow of germplasm and thus the development of new crop varieties, an outcome that is in no one's interest. Important non-monetary benefits can arise from international collaboration in the conservation and use of genetic resources. Non-monetary benefits include access to more germplasm and improved material than can be found in any one country as well as to training opportunities, new technologies and information arising from the use of exchanged material. International collaboration brings with it increased opportunities for developing joint strategies and activities for conserving and using genetic resources and for sharing responsibilities and costs. In general, the more parties that are involved in a collaborative relationship, the more widely the costs and benefits can be shared, thus reducing the burden and increasing the advantage to all partners. While the authors argue strongly in favour of a multilateral approach to access and benefit sharing, they observe that important non-monetary benefits can also arise from bilateral arrangements. They describe a series of recent plant explorations in Ecuador, supported by the United States Department of Agriculture (USDA), as a good example of a bilateral arrangement that has yielded significant non-monetary benefits to both countries. Networks, such as the International Network on Genetics in Aquaculture and the International Network for Genetic Evaluation of Rice, serve as multilateral exchange arrangements and the means for sharing resources, ideas, technologies and information amongst a wide range of participants. The Consultative Group on International Agricultural Research (CGIAR) provides a framework for a global multilateral system. In return for providing access to their germplasm, the CGIAR's partners gain no-cost access to value-added products, secure conservation, restoration, information and a wide range of basic and improved germplasm. Together, the Future Harvest Centres supported by the CGIAR exchange approximately 150 000 accessions and 500 000 samples of improved material each year, along with the related technology and information.